A Method of Obtaining Geonoiseprotective Foam Concrete for Use on Railway Transport. (2017) - Sychova, Anastasia; Sychov, Maxim; Rusanova, Ekaterina
Abstract: The article presents the method of production of foam concrete, as a geonoiseprotective material. Its ability to absorb acoustic energy due to porous structure, composition and thickness of foam films is taken into account. Besides that the energy-absorbing ability of the solid phases of the stone frame is taken into consideration. The possibility of using this foam concrete as a material for reducing noise from the railway transport movement is shown. Also, the method takes into account geoprotective properties of the material concerning the pollution from railway transport.